1984
DOI: 10.1139/x84-052
|View full text |Cite
|
Sign up to set email alerts
|

Development of tanoak understories in conifer stands

Abstract: The stocking, age, and growth rates of tanoak (Lithocarpusdensiflorus [Hook and Arn.] Rehd.) were studied in the understory of 13 Douglas-fir (Pseudotsugamenziesii [Mirb] Franco) and mixed conifer stands, 53–240 years old, on a range of sites in Oregon and California. The understory was uneven in both age and size in all stands. Tanoak <2.0 cm diameter at breast height (dbh) ranged from 1 to 62 years old and from 5 to 216 cm tall. The stems of tanoak >2.0 cm dbh ranged from 18 to 98 years old and from 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…An individual seedling may die back several times and produce one to seven new stems with the largest stem being the oldest. On the basis of scores of samples, Tappeiner and McDonald (1984) found no reliable relationship between the age and size of the above-ground stem and the total age of tanoak seedling-sprouts. However, the total age of seedling-sprouts can be ascertained quite accurately by counting the xylem rings in the stem below the burl.…”
Section: Seedling-sproutsmentioning
confidence: 85%
See 2 more Smart Citations
“…An individual seedling may die back several times and produce one to seven new stems with the largest stem being the oldest. On the basis of scores of samples, Tappeiner and McDonald (1984) found no reliable relationship between the age and size of the above-ground stem and the total age of tanoak seedling-sprouts. However, the total age of seedling-sprouts can be ascertained quite accurately by counting the xylem rings in the stem below the burl.…”
Section: Seedling-sproutsmentioning
confidence: 85%
“…The burl on tanoak seedlings develops slowly and is strongly related to age and site quality (Tappeiner and McDonald 1984). It is just as likely to produce sprouts in a sun environment as in a shade environment; however, the number of stems tends to be less in shade ( fig.…”
Section: Seedling-sproutsmentioning
confidence: 99%
See 1 more Smart Citation
“…Available data are inadequate to predict the effects of repeated fires in redwood forests, but it is possible that frequent burning may gradually reduce the abundance of tanoak. Tappeiner and McDonald (1984) noted that stumps of tanoak less than 2 cm DBH sprouted ''much less vigorously'' than stumps of larger tanoak, and Kauffman and Martin (1990) found that the probability of whole plant mortality decreased significantly with increasing v www.esajournals.org pre-fire aboveground biomass of shrubby tanoaks, suggesting that if adequate recovery has not occurred between fire events, root systems may not survive. Donato et al (2009) found a similar pattern for all hardwoods pooled (tanoak was not analyzed separately), and documented that the percent cover of tanoak, two years postfire, was lower in a ''short interval'' burn area than in the ''long interval'' burn area; however, they also noted that this difference was slight and concluded that a ''short interval'' (15 years) should allow for indefinite site persistence.…”
Section: Main Findingsmentioning
confidence: 99%
“…The competition from tanoak after cutting is directly proportional to the amount of cover before cutting (Tappeiner and McDonald 1983). Tanoak builds a basal burl early in life that is protected from surface disturbance (fire and cutting) and is capable of resprouting.…”
Section: The Seriesmentioning
confidence: 99%